LETTUCE DISEASES IN HYDROPONIC CULTIVATION IN THE METROPOLITAN GREEN BELT OF CURITIBA, PARANÁ STATE, BRAZIL - SILVA, Michele Strapasson Caillet da; LIMA NETO, Vismar da Costa (Scientia Agraria, 2007)
During surveys carried out in 2003 and 2004, covering ten lettuce (Lactuca sativa L.) growing properties in five municipalities of the green belt of Curitiba, the following diseases were identified: downy mildew (Bremia lactucae), powdery mildew (Oidium sp.) rhizoctoniosis (Rhizoctonia solani), sclerotiniosis (Sclerotinia sclerotiorum) bacterial soft rot (Pectobacterium carotovorum), and Lettuce mosaic virus. Also, the lettuce big vein-associated and Mirafiori lettuce virus, responsible by the lettuce big vein syndrome. The diseases were found in fields of all five municipalities. Downy mildew, Lettuce mosaic virus, big vein viral complex, rhizoctoniosis and sclerotiniosis were prevalent in colder months, while powdery mildew and bacterial soft rot prevailed in hotter months.